2001
DOI: 10.1089/08977150150502622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enriched Housing on Functional Recovery After Spinal Cord Contusive Injury in the Adult Rat

Abstract: To date, most research performed in the area of spinal cord injury focuses on treatments designed to either prevent spreading lesion (secondary injury) or to enhance outgrowth of long descending and ascending fiber tracts around or through the lesion. In the last decade, however, several authors have shown that it is possible to enhance locomotor function after spinal cord injury in both animals and patients using specific training paradigms. As a first step towards combining such training paradigms with pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 60 publications
7
76
0
1
Order By: Relevance
“…CatWalk measures a large number of both static and dynamic gait parameters and enables quantitative assessment of locomotion. 33,[35][36][37][38][39] Briefly, the CatWalk system consists of a glass runway that contains light from a fluorescent tube. Internal reflection causes the light to be restricted to the glass surface plate under normal circumstances.…”
Section: Catwalk-automated Quantitative Gait Analysismentioning
confidence: 99%
“…CatWalk measures a large number of both static and dynamic gait parameters and enables quantitative assessment of locomotion. 33,[35][36][37][38][39] Briefly, the CatWalk system consists of a glass runway that contains light from a fluorescent tube. Internal reflection causes the light to be restricted to the glass surface plate under normal circumstances.…”
Section: Catwalk-automated Quantitative Gait Analysismentioning
confidence: 99%
“…This increased corticospinal drive could come from plasticity occurring in the cortex (see aforementioned data) or in the descending pathways themselves. In rodents after incomplete SCI, increased activity via enriched environment promotes plasticity in spared corticospinal but not raphespinal or rubrospinal axons [75]. * Based on studies in animal models, a possible molecular mechanism has been proposed for the neuroplasticity events known to occur because of voluntary exercise after SCI.…”
Section: Active Exercisementioning
confidence: 99%
“…Lankhorst et al (36) found improvement in the Basso, Beattie and Bresnahan (BBB) locomotor test (37), BBB subscale, Gridwalk test, CatWalk test, and thoracolumbar height test in animals placed in an enriched environment immediately after SCI.…”
Section: Introductionmentioning
confidence: 99%